The role of social support in the relation between different coping strategies and emotional distress in bereaved elderly - Ljevaja, Milica; Janić, Ognjen; Lazić, Milica; Krstić Joksimović, Kristina (Psihološka istraživanja, 2023)
The aim of this study is to explore does social support (emotional and instrumental) has a moderating effect on the relation between coping strategies – loss-oriented and restoration-oriented – and emotional distress. In this research participated 64 respondents who experienced a death of a spouse in the last 40 days. They were uniformed in terms of gender, with age ranging from 65 to 89. Moderators were measured on one-item scale, while predictors were measured with 22-item Inventory of Daily Widowed Life (IDWL; Caserta & Lund, 2007). Emotional distress was measured with The Depression, Anxiety and Stress Scale (DASS-21, Lovibond & Lovibond, 1995). Results indicated the following. When the predictor variable was loss orientation, and the moderator was emotional and instrumental support, significant main and interactive effects on emotional distress were registered. Namely, in conditions of low loss orientation, elderly who had higher social support had lower emotional distress than elderly who had lower social support. However, in conditions of high loss orientation, individuals achieved equal scores on the emotional distress scale regardless of the level of social support. When restoration orientation was the predictor, and emotional support was the moderator, both main and interactive effects were registered. Thus, in conditions of low restoration orientation, elderly with higher emotional support had a lower score on the emotional distress scale than those with lower support. In conditions of restoration orientation, regardless of the level of emotional support, elderly achieved approximately same values ​​on the scale of emotional distress.
Keywords: bereavement; social support; emotional distress; dual process model; elderly